Perceived determinants of implementation success of the neglected tropical diseases programme in Ghana: a qualitative study among programme officers - Desmond Dzidzornu Otoo (BMC, 2021)
Abstract Background The importance of health policy implementation cannot be overemphasized in contemporary public health. Neglected Tropical Diseases (NTDs) have negatively impacted society, affect quality of life and make the poor societies poorer. Several policies and strategies have been put in place across the world including the neglected tropical diseases programme in Ghana. Though chalked many successes, the programme continues to lag behind in the full attainment of various objectives. Several factors exist that determine how effective a programme is implemented. Identification of these factors on every programme is essential to determine where more programme resources need to be channelled. This study assessed the determinants of successful implementation of the neglected tropical diseases programme in Ghana. Methods A qualitative approach with the case study design was employed. Purposive and snowball sampling techniques were used to identify key programme officers at the national, regional and district levels of programme implementation. Eighteen (18) Key informant interviews were conducted at all the three levels of the Ghana Health Service NTDs programme. Data were thematically analysed and presented. Results Findings from the study revealed that determinants that influenced the successful implementation of the NTDs programme include donor support, education and training, partnerships, reliability of the health structure, integrative nature of the programme and management commitment. These determining factors cut across the inner settings of the implementing agency and the external environment. Conclusion Neglected tropical diseases continuously affect Ghanaians, especially the poor. It is important for both policy makers and implementers to identify the factors that ensure the success of the programme in the Ghanaian context. Though the factors are independently sufficient, they synergistically lead to improved programme implementation. Empowering all units involved (local to national level) and maximizing the enabling factors identified to would improve upon implementation and ensure sustainability.